Enhancing Pedagogical Competence in Inclusive Kindergarten Settings: The Effectiveness of Learning Communities as Professional Development Strategy - Susmawati, Eko; Sukinah, Sukinah (Journal of Innovation and Research in Primary Education, 2025)
Inclusive kindergarten education requires teachers with sophisticated pedagogical competencies to address diverse learning needs. However, significant deficiencies exist in pedagogical competence among Indonesian teachers in inclusive settings, largely due to varying educational backgrounds and insufficient understanding of children with special needs. Learning communities have emerged as promising collaborative frameworks for professional development, yet limited research examines their effectiveness in enhancing pedagogical competence within inclusive early childhood education contexts.This study investigated the effectiveness of learning communities (KOMBEL) in enhancing pedagogical competence among inclusive kindergarten teachers, analyzing specific competence aspects that experience improvement and examining factors influencing implementation success. A descriptive quantitative design was employed with seven teachers at TK Negeri 1 Teluk Pandan using saturated sampling. Data collection utilized validated questionnaires and structured observations with pre-test and post-test measurements. The pedagogical competence assessment covered six dimensions: understanding inclusive children's characteristics, learning planning, teaching methods, classroom management, assessment, and reflective capabilities. Statistical analysis employed paired-samples t-tests and descriptive analysis using SPSS 25.0.Significant improvement in pedagogical competence was observed, with mean scores increasing from 13.71 to 25.00 (82% enhancement). Statistical analysis confirmed significant differences (p < 0.000) with large effect size (Cohen's d = 7.04). All six pedagogical competence dimensions showed substantial improvement, with teaching methods and strategies demonstrating the most dramatic enhancement (2.1 to 4.3 on five-point scale). Learning communities effectively enhance pedagogical competence among inclusive kindergarten teachers through collaborative professional development. The substantial improvements across all competence dimensions validate learning communities as systematic strategies for addressing pedagogical deficiencies in inclusive education settings.